If You Teach It, Will They Come? Law Students, Class Attendance and Student Engagement - Lillian Corbin (Legal Education Review)
This article considers whether the techniques and philosophy of a ‘Nurturing’ teacher can be justified in the law school context. In doing this, the article explores two interrelated issues. The first is the effect of students’ emotions on their ability to learn effectively. The second is the role of the teacher in being aware of and harnessing these emotions in order to create the optimal classroom environment for effective learning. The article argues that the techniques and philosophies of a Nurturing teacher appropriately take account of the emotional aspect of student learning, and are therefore appropriate to law school teaching.